The effect of interactivity on memory. - Tan, Angeline Jac Lynn. (2011)
The present study seeks to determine if a passive observer’s memory differs from those who are actively involved. To investigate this issue, we examined whether memory for details of an event will be enhanced, impaired, or unaffected when participants are involved (making decisions) at various points in an event. Results showed that memory of passive observers are equivalent with actors regardless of the relevance of decision making. In addition, there was a significant decline in memory after making decisions that were relevant to the context, but not when decisions were un-relevant. This indicates interference in memory when making decisions that are related to the context. The theoretical implications of these data in understanding the nature of interactivity and memory are discussed.